Paradigma Teori Humanistik Dalam Pendidikan : Teoritis dan Praktis Dalam Proses Pembelajaran - Asroriyah Asroriyah; Abdullah Ahmadinejaf; Yuni Nur Irmalia; M Yunus Abu Bakar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine humanistic learning theory and its application in education. This theory emphasizes that every individual has the potential to develop optimally through the fulfillment of needs and the achievement of self-actualization. The key figures in this theory are Abraham Maslow, Carl Rogers, and Arthur W. Combs. Maslow explains the hierarchy of needs as the basis of learning motivation; Rogers emphasizes freedom in learning; while Combs highlights the importance of self-perception in influencing learning behavior. This study employs a literature review method by analyzing various sources such as books and scientific journals. The data were analyzed using descriptive qualitative methods. The results of the study indicate that the humanistic approach is capable of creating meaningful learning, increasing motivation, and encouraging student engagement. Furthermore, this approach also helps develop potential, foster a positive self-concept, and enhance problem-solving skills. Thus, the humanistic theory is important to apply in education because it supports the holistic development of students—cognitive, affective, and psychomotor.